Pengaruh Usia Perusahaan terhadap Kinerja Keuangan (Studi pada Bank Victoria Syariah) - Jeffry Andhika Putra (Universitas Widya Mataram, 2021)
Company age and experience are concepts that remain the same. Younger and older companies differ in experience and other aspects. The company's innovation activities change over time and the age of the company reflects the process of growth and accumulation of experience. Age is considered an important determinant of corporate innovation because of its learning effect, which enables mature companies to innovate more effectively as they build on previous routines and capabilities. Over time, companies can not only innovate based on past experience and capabilities, but can also accumulate resources, managerial knowledge, and the ability to handle uncertainty. The purpose of this study was to determine the effect of company age on financial performance, as measured by return on assets (ROA) and return on equity (ROE). The results of the regression analysis show that the age of the company has no effect on ROA and ROE. Based on the results of this study, the management of Bank Victoria Syariah should try to increase market share to increase financial performance, for example by intensifying promotions and corporate cooperation.